2003
DOI: 10.1046/j.1460-9568.2003.02511.x
|View full text |Cite
|
Sign up to set email alerts
|

Pedunculopontine tegmental stimulation evokes striatal dopamine efflux by activation of acetylcholine and glutamate receptors in the midbrain and pons of the rat

Abstract: The pedunculopontine tegmental nucleus appears to influence striatal dopamine activity via cholinergic and glutamatergic afferents to dopaminergic cells of the substantia nigra pars compacta. We measured changes in striatal dopamine oxidation current (dopamine efflux) in response to electrical stimulation of the pedunculopontine tegmental nucleus using in vivo electrochemistry in urethane-anaesthetized rats. Pedunculopontine tegmental nucleus stimulation evoked a three-component change in striatal dopamine eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(141 citation statements)
references
References 88 publications
(140 reference statements)
6
135
0
Order By: Relevance
“…These results are consistent with the critical role of M5 receptors in prolonged activation of mesolimbic and striatal dopamine neurons following mesopontine stimulation Forster and Blaha, 2003). Consequently, M5 mutant mice may serve as a model of reduced dopamine function, and M5 blockers may be useful as neuroleptic drugs.…”
Section: Chromosomal Localization Of Mouse and Human M5 Muscarinic Resupporting
confidence: 85%
See 1 more Smart Citation
“…These results are consistent with the critical role of M5 receptors in prolonged activation of mesolimbic and striatal dopamine neurons following mesopontine stimulation Forster and Blaha, 2003). Consequently, M5 mutant mice may serve as a model of reduced dopamine function, and M5 blockers may be useful as neuroleptic drugs.…”
Section: Chromosomal Localization Of Mouse and Human M5 Muscarinic Resupporting
confidence: 85%
“…Pharmacological studies suggest that M5 receptors tonically regulate mesolimbic and striatal dopamine functions (Blaha et al, 1996;Miller and Blaha, 2002;Zhang et al, 2002;Basile et al, 2002;Forster and Blaha, 2003). Since decreased dopaminergic activity in the nucleus accumbens enhances latent inhibition in rats (Joseph et al, 2000;Moser et al, 2000;Russig et al, 2002;Gray et al, 1997), the improvement in latent inhibition in M5 mutant mice appears to result from decreased mesolimbic dopamine activation by M5 receptors.…”
Section: Latent Inhibitionmentioning
confidence: 99%
“…The convergence of these inputs has raised the possibility that both neurotransmitters may be coreleased from the same terminals, with some evidence that this does occur in the squirrel monkey but not in the rat (Lavoie and Parent, 1994;Wang and Morales, 2009). Stimulation of the PPT elicits burst firing in SN pars compacta dopamine neurons (Lokwan et al, 1999;Floresco et al, 2003) and evokes dopamine release in the striatum, which is inhibited by application of either nicotinic or glutamatergic receptor antagonists into the SN pars compacta (Futami et al, 1995;Forster and Blaha, 2003). Indeed, it has been suggested that cholinergic activation is critical for promoting burst firing (Kitai et al, 1999).…”
Section: Pedunculopontine Nucleusmentioning
confidence: 99%
“…The PPTg contains cholinergic and glutamatergic cells that project to the ventral tegmental area (VTA) and the substantia nigra (Beninato and Spencer, 1987;Bolam et al, 1991;Futami et al, 1995). Stimulation of these afferents activates midbrain DA cells with short latency (Scarnati et al, 1984;Lokwan et al, 1999) and evokes DA release in the areas of dopaminergic innervation (Forster and Blaha, 2003).…”
Section: Introductionmentioning
confidence: 99%